2011
DOI: 10.1080/01434632.2011.558901
|View full text |Cite
|
Sign up to set email alerts
|

Young people's representations of language brokering

Abstract: In recently arrived immigrant families, children and young people often act as language brokers for their parents and other adults. In public and academic debate, this activity is sometimes portrayed negatively as imposing excessive burdens of responsibility on the young people. This paper reports an analysis of qualitative data from a broader study of young people's representations of conflicting roles in child development. Interview participants were monolingual and bilingual students, aged 15Á18 years. Half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 16 publications
2
13
1
3
Order By: Relevance
“…[34] In immigrant families children and young people often act as language brokers for their parents. [35] Findings in the present study have no clear indications that the daughters of the critically ill immigrant fathers were language brokers. On the other hand, the daughters have grown up in a society where they have learned the Norwegian language, which was different for their fathers.…”
Section: Being Intertwined Between the Western Hospital Culture And Tcontrasting
confidence: 51%
“…[34] In immigrant families children and young people often act as language brokers for their parents. [35] Findings in the present study have no clear indications that the daughters of the critically ill immigrant fathers were language brokers. On the other hand, the daughters have grown up in a society where they have learned the Norwegian language, which was different for their fathers.…”
Section: Being Intertwined Between the Western Hospital Culture And Tcontrasting
confidence: 51%
“…After the full interviews had been transcribed, a Framework Analysis strategy was employed to investigate variation within the sample (Pope et al 2000). The key findings from the analysis of group differences in the full sample may be studied in detail in Cline et al (2011). For this paper we selected a purposive sample of four students whose personal histories and family situations were typical of those represented in the larger group in the original sample.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports on this study have focused on young people's representations of "work" (Crafter et al 2009) and on the early assumption of adult-like responsibilities as a young carer (O'Dell et al 2010). We examined young people's representations of language brokering in a study that investigated how people's direct experience of that activity and of bilingualism might have influenced the views that are developed (Cline et al 2011). The aim of that analysis was to clarify the impact of personal experience of the CLB process by comparing the views of young people who reported that they had performed CLB activities with those of a group of bilingual speakers who had not, and also with those of a group of monolingual speakers living in the same areas of England where there had been significant recent immigration.…”
Section: Introductionmentioning
confidence: 99%
“…Research also points to some positive dimensions such as pride (e.g. Orellana, 2003) and to a perception in multilingual areas that such activity is just a normal thing to do when one is bilingual (Cline et al 2011).…”
Section: The Advantages and Disadvantages To Child Language Brokeringmentioning
confidence: 99%
“…We have argued elsewhere (Cline et al 2014a) that the lack of official policy guidance reflects an ambivalent attitude to the practice of language brokering that permeates professional and academic commentary on the subject of secondlanguage use and bilingualism more generally. Even within increasingly 'super-diverse' locations within the UK (see Vertovec, 2005), monolingualism is still perceived as the prevailing practice, whilst multilingualism is only vaguely understood (Cline et al 2011), and in some cases, explicitly viewed as negative (Brutt-Griffler & Varghese, 2004). In locations of high language diversity, the home languages of many immigrants are socially devalued and in some cases, actively suppressed in institutional settings like school (Cummins, 2000).…”
Section: The Importance Of the School Contextmentioning
confidence: 99%